Analysis of the Application of Risk Management in Financing Mudharabah At PT. BPRS Gebu Prima - Cindy Arianti; Salman Nasution (Britain International for Academic Research (BIAR) Publisher, 2023)
The purpose of this study is to ascertain how PT BPRS Gebu Prima manages the risks associated with mudharabah financing and financing problems. This study is qualitative, and the data were gathered through direct observation, documentation and interviews. The exploration results were obtained by analysts straight by taking part in mudharabah supporting exercises completed at PT BPRS Gebu Prima. The risk on the board at this bank is completed in three phases, the first is the arranging stage which incorporates the exercises of ending connections and actually taking a look at the report on the occurrences of forthcoming clients. The subsequent stage is the execution stage which contains study exercises and supporting examinations by bookkeepers that pay attention to the 5C standards (Character, Limit, Capital, Assurances and Conditions). In addition, the control phase, which includes activities for monitoring financing's use and installments, is the third stage. The gamble the board execution process is done as per existing methods. The process of identifying risks aims to identify and prevent risks from the beginning, thereby preventing losses.